144k views
3 votes
4.

Here is the proof of (sin x - cos x)2 = sec2 x - tan2 x - 2sin x cos x.
What is the missing line

1 Answer

0 votes

Answer:

See Explanation Below

Explanation:

Given


(sin x - cos x)^2 = sec^2x - tan^2x - 2sinx.cos x.

Required

Prove

To start with; we open the bracket on the left hand side


(sin x - cos x)^2 = (sin x - cos x)(sin x - cos x)


(sin x - cos x)^2 = (sin x )(sin x - cos x)- (cos x)(sin x - cos x)


(sin x - cos x)^2 = sin^2 x -sinx cos x - sin xcos x + cos^2 x


(sin x - cos x)^2 = sin^2 x -2sinx cos x + cos^2 x

Reorder


(sin x - cos x)^2 = sin^2 x + cos^2 x - 2sinx cos x

From trigonometry;


sin^2x + cos^2x = 1

So;


(sin x - cos x)^2 = sin^2 x + cos^2 x - 2sinx cos x

becomes


(sin x - cos x)^2 = 1 - 2sinx cos x

Also from trigonometry;


sec^2x - tan^2x = 1

So,


(sin x - cos x)^2 = 1 - 2sinx cos x

becomes


(sin x - cos x)^2 = sec^2x - tan^2x - 2sinx cos x

Proved

User Daveraja
by
5.0k points